2016
DOI: 10.1007/s11010-016-2690-5
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of HDAC9 promotes oral squamous cell carcinoma growth, regulates cell cycle progression, and inhibits apoptosis

Abstract: Histone deacetylases (HDACs) are a family of deacetylase enzymes that regulate the acetylation state of histones and a variety of other non-histone proteins including key oncogenic and tumor suppressor proteins, which modulates chromatin conformation, leading to regulation of gene expression. HDACs has been grouped into classes I-IV and histone deacetylase 9 (HDAC9) belongs to class IIa which exhibits tissue-specific expression. Recent reports have demonstrated both pro-oncogenic and tumor suppressive role for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 49 publications
2
55
0
Order By: Relevance
“…Previous studies have also reported the expression and functional roles of HDAC9 in various types of cancer. Upregulated expression of HDAC9 was identified to promote oral squamous cell carcinoma growth and cell cycle progression through targeting of the transcription factors myocyte enhancer factor 2D and nuclear receptor subfamily 4 group A member 1 (37). Additionally, a study by Zhao et al (38) demonstrated that HDAC9 epigenetically repressed the transcription of p53 via binding to its proximal promoter region, thus enhancing the proliferation of osteosarcoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also reported the expression and functional roles of HDAC9 in various types of cancer. Upregulated expression of HDAC9 was identified to promote oral squamous cell carcinoma growth and cell cycle progression through targeting of the transcription factors myocyte enhancer factor 2D and nuclear receptor subfamily 4 group A member 1 (37). Additionally, a study by Zhao et al (38) demonstrated that HDAC9 epigenetically repressed the transcription of p53 via binding to its proximal promoter region, thus enhancing the proliferation of osteosarcoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Histone deacetylases (HDACs) promote transcriptional repression and gene silencing by creating the non‐permissive chromatin. HDAC1 (Kumar, Yadav, Lang, Teknos, & Kumar, ; Theocharis et al, ), HDAC2 (Chang et al, ; Theocharis et al, ), HDAC6 (Sakuma et al, ), HDAC8 (Ahn & Yoon, ), and HDAC9 (Rastogi et al, ) were upregulated in OSCC tissues and associated with advanced stages (Chang et al, ; Sakuma et al, ), reduced OS (Chang et al, ; Rastogi et al, ; Theocharis et al, ), and poor prognosis (Chang et al, ). Specifically, HDAC1 overexpression demonstrated correlations with younger age, male gender, poor differentiation, shorter DFS, and metastases (Theocharis et al, ), and high HDAC2 abundance was associated with advanced T and N status (Chang et al, ).…”
Section: Histone Modifications In Osccmentioning
confidence: 99%
“…HDAC2 boosted cell invasion and migration and regulated tumorigenesis and progression in mice (Chang et al, ). Overexpression of HDACs were found in HNSCC cell lines as well (Ahn & Yoon, ; Kumar et al, ; Rastogi et al, ; Sakuma et al, ). Sir2 homolog SIRT1 expression and catalytic activity were both elevated in OSCC cells (Xiong, Li, Tang, & Chen, ).…”
Section: Histone Modifications In Osccmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, Hdacs are potential therapeutic targets for some neoplasms. Previous studies have demonstrated that Hdac inhibitors can induce cell cycle arrest, apoptosis and tumor cell differentiation (9,10). Several Hdac inhibitors have been studied in patients with solid neoplasms or other malignancies, and are considered potential anticancer drug candidates (11,12).…”
Section: Introductionmentioning
confidence: 99%